ART-PEDAGOGICAL TECHNOLOGIES IN VOCATIONAL EDUCATION - Rzhevska, Nataliia (Збірник наукових праць Уманського державного педагогічного університету, 2020)
This article is dedicated to the use of art-pedagogical technologies in the educational process of professional training of future specialists. The data obtained during a pedagogical experiment provide rationale for the fact that the current art-pedagogical methods are intended to train specialists to implement a set of conditions necessary for the development of future graduates’ eligibility for employment and further professional efficiency. Also, based on the data obtained, we can say that most students having defined the leading type of perception were visuals. The analysis of psychological and pedagogical sources allows us to conclude that, when it comes to art-pedagogical technologies, it is necessary to clearly understand the root cause of the necessity for their application, since it defines the level of the specialist’s professional training required for their use.